Heterojunction Technology vs. Passivated Emitter and Rear Contact Photovoltaic Panels: Evaluating Efficiency and Profitability Under Challenging Summer Conditions in Lisbon Using Extensive Field Data - André Sapina; Paulo Branco (Energies)
Renewable energy is essential for reducing fossil fuel dependence and achieving carbon neutrality by 2050. This study compares the widely used passivated emitter and rear contact (PERC) cells with advanced heterojunction technology (HJT) cells. Conducted in Lisbon during August 2022, this research evaluates the energy yield of PV installations over 400 W under challenging summer conditions. HJT cells, which combine monocrystalline silicon and amorphous layers, showed a 1.88% higher efficiency and a 3% to 6% increase in energy yield compared to PERC cells. This study also examines the effects of irradiance and temperature on performance using experiment field data. HJT modules are ideal for limited space or power constraints, offering long-term profitability, while PERC modules are more cost-effective for budget-limited projects.